2021
DOI: 10.3390/su14010414
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advances in Aviation Electrification: Enhancing Strategic R&D Investment Analysis through Simulation Decomposition

Abstract: Computational decision-making in “real world” environmental and sustainability contexts frequently requires the need to contrast numerous uncertain factors and difficult-to-capture dimensions. Monte Carlo simulation modelling has frequently been employed to integrate the uncertain inputs and to construct probability distributions of the resulting outputs. Visual analytics and data visualization can be used to support the processing, analyzing, and communicating of the influence of multi-variable uncertainties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…SimDec reveals previously unrecognized connections between the inputs and the outputs by visually mapping the relative contributions from each scenario onto the output distribution (Kozlova and Yeomans, 2020). This visualization permits the consequences of different combinations of the states to become recognizable to decision-makers in a straightforward manner (Kozlova and Yeomans, 2021). As the states can reflect different degrees of risks, SimDec actually generates important actionable insights to support decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SimDec reveals previously unrecognized connections between the inputs and the outputs by visually mapping the relative contributions from each scenario onto the output distribution (Kozlova and Yeomans, 2020). This visualization permits the consequences of different combinations of the states to become recognizable to decision-makers in a straightforward manner (Kozlova and Yeomans, 2021). As the states can reflect different degrees of risks, SimDec actually generates important actionable insights to support decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…This paradox was actually shown to produce ill-designed environmental incentives for the companies. Electrification of regional aviation was analyzed with SimDec through the lens of increased flying range of electric aircraft as a function of improved battery capacity and motor power (Kozlova et al, 2021). As with the previous case (Deviatkin et al, 2021), a critical interaction was revealed via the SimDec analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a life-cycle-oriented sustainability assessment of emerging aircraft technologies is investigated in [7] to identify these hotspots and problem shifts and provide further guidance for actions aimed at sustainable aviation development at an early stage. Additionally, technical advances in aviation electrification are explored to enhance strategy research and development investment analysis in [8].…”
Section: Introductionmentioning
confidence: 99%